IMPROVING READING COMPREHENSION IN RECOUNT TEXT USING THE QUESTION-ANSWER RELATIONSHIP STRATEGY - Nabilla Dwi Dika Damas Tatik; Iwan Kurniarahman (JEELL (Journal of English Education, Linguistics and Literature), 2024)
This study investigated the effectiveness of the Question-Answer Relationship (QAR) Strategy to improve Reading Comprehension of the recount text. Using a quasi-experimental design, this study involved 76 students from MTsN 3 Kediri. The experimental group consisted of 38 students from class VIII-G who were treated using the QAR strategy, while the other 38 students from class VIII-D were in the control group with the Sustained Silent Reading (SSR) strategy. Analysis of Covariance (ANCOVA) was used to compare the effectiveness of the two strategies. The study results revealed that the Mean score for the experimental group was 75.79, whereas the control group scored 71.71 on average. The ANCOVA analysis indicated a significant value of 0.000, lower than the threshold of 0.05, suggesting that the QAR strategy was more successful in improving reading comprehension compared to the SSR strategy. Students taught using the QAR Strategy outperformed those taught using the SSR Strategy in comprehending recount texts.